4q- Syndrome By Interstitial Deletion 4 (Q22Q25) De Novo In A Term Newborn - Talavera-Vargas-Machuca, Sergio (2017)
We describe the case of a male term neonate with psychomotor development anomalies, craniofacial defects, limbs and genital anomalies, born at Instituto Nacional Materno Perinatal in which an interstitial chromosomal deletion was found in the long arm of chromosome 4. The karyotype of the newborn was 46, XY, del (4) (q22q25) de novo. The phenotypic traits observed in the propositus were compatible with 4q- syndrome.